"Garri" atzizkiaren izaera bikoitzaz: zergatik den maitagarria bezain mingarria - Artiagoitia, Xabier (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1995)
The Basque suffix garri is traditionally characterized as forming adjectives from verbs and disputably, from nouns or adjectives and as having both an active and a passive meaning. This study first establishes on several grounds that garri is basically a deverbal suffix which forms adjectives productively. Secondly, it is shown (a) that the so-called passive value of the suffix is restricted to diadic transitive verbs: the internal argumental of the verb becomes the external one of the adjective; and (b) that the so-called active value of the suffix is restricted to psych verbs with experiencer objects (cf. the preocuppare/kezka(tu) class): the surface subject of the verb becomes the external argument of the adjective. Thirdly, a unified characterization of the garri suffixation is proposed along the lines of Grimshaw (1990): if subjects of kezka(tu) verbs are internal arguments of the verb, the rule of garri suffixation simply adds an R argument which binds the deepest internal argument of a diadic verb. Finally, verbs whose surface subject bear an instrumental θ-role are considered. Since these, too, admit the suffix garri (the surface subject becomes the external argument of the deverbal adjective), I suggest that instrumental subjects must count as internal arguments in Basque in order to maintain a uniform rule of garri suffixation.